Seleksi Sumber Daya Manusia di SMP IBS Kiai Demak Purwakarta - Zakiah, Nurfitriani Fitrotu (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
The achievement of an institution or company depends on the acceptance of Human Resources (HR) in an institution or company. To get quality Human Resources, an institution must hold a selection to get quality employees. Then, to get quality employees, an institution must prepare a unique strategy during the selection process. The goal is to provide the organization with an effective work unit. To achieve this goal, the study of human resource selection will show how companies should acquire, develop, use, evaluate, and maintain the correct number (quantity) and type (quality) of employees. Therefore, Kiai Demak Pondok Salam IBS Islamic Boarding School also carried out a strategy in selecting its employees so that the Kiai Demak IBS Islamic Boarding School has employees or teachers who have quality according to their fields that they can make Kiai Demak IBS Islamic Boarding School more advanced in the future. In the HR selection process, there are several ways for Islamic Boarding School Kiai Demak to use two methods, namely scientific and non-scientific.